Truth as a sociocultural phenomenon: modern interpretation - Volnistaya, Marina G.; Korkiya, Eka D.; Mamеdov Agamali K. (Journal of the Belarusian State University. Sociology, 2020)
The history of science in any of its transformations and metamorphoses is, in fact, a search for and definition of the truth. As an example, I. Kant’s famous four questions start with the question «What can I know?». Thus, the search for truth as a subject of research has been a dominating force throughout human history. Of course, sociology as a social meta-science is also involved in this topic. A simple assertion of the existence of three concepts of truth, namely accordance, agreement and advantage, does not fully answer the prerequisites of contemporary discourse. The present article analyses a new discourse on the study of truth in contemporary science. We give a brief retrospective analysis of the main fields of truth interpretation. At the same time, these directions are not just listed but linked into the general outline of contemporary epistemology. Of course, a greater bias is made towards the sciences of the social and humanitarian profile. That, however, does not exclude the necessary portion of the data of natural science research. In the article these data are not used as demonstrations, but as independent meta-scientific research. We give various examples of the complementarity of different branches of science. In particular, we show the scope and relative limitation of such concepts as correspondence theory, evolutionary epistemology, socio-humanitarian cybernetics, adaptationism and neo-adaptationism. A significant place in the article is occupied by the problem of truth in artistic creation. We also give sustainable conclusions about the polyphonicity of truth and its flickering character.